NETWORK EXTERNALITIES AND MARKET COMPETITIVENESS - Radosław Szulc (Contemporary Economy, 2017)
All companies operate and compete on the cybermarket according to a click-and-mortar or pure-play business model. This alternative can be recognized as a factor in their competitiveness. The principal problem which requires a more in-depth treatment is how to explain the marginal theory in the cybermarket environment, where the law of diminishing returns does not apply, while growing revenues are a reality. Also, a network externality is a controversial issue, which is perceived as an impact factor affecting the competitive processes between all the players of the cybermarket. Network externalities are related to endeavours by companies for the standardisation of network goods, which is also perceived as a barrier to cybermarket competitiveness. The aim of this paper is to consider how competitiveness processes, e.g. entry of new market players, operate in markets with network externalities and how such processes determine the competitiveness of these markets.